Laboratory and industrial testing of silica bricks for coke ovens - Camerucci, Maria Andrea (2008)
In order to rationalize the reconstruction of coke ovens' walls in a local steelmaking, a set of laboratory and industrial tests was carried out on silica KN bricks. Two types of bricks that are currently used in oven construction were analyzed, one being less expensive than the other. On the other hand, 25 year-old original bricks were also studied. The results of laboratory tests were analyzed taking into account the requirements of DIN 1089 standard. Additionally, an evaluation of costs was carried out.